Microcystic lymphatic malformation presenting as firm, skin‐colored papules of the lips. Issue 6 (23rd June 2022) - Edminister, John R.; Zarbo, Allison; Seale, Lauren; Friedman, Ben J.; Shwayder, Tor
Abstract: Microcystic lymphatic malformation (MiLM), also known as lymphangioma circumscriptum, is a superficial collection of lymphatic vessels measuring <1 cm in the largest diameter, often with a more extensive deeper malformation. It commonly presents as discrete or grouped plaques of clear or hemorrhagic vesicles classically described as "frogspawn"; however, here we describe a case of its unique presentation as firm papules on the lips of a healthy six‐year‐old child. These skin‐colored papules in the absence of vesicles with lymphatic and/or hemorrhagic fluid may not be clinically indicative of MiLM. This case represents a diagnostic challenge due to the unique morphology of pink, fleshy papules as opposed to the clear or hemorrhagic vesicles typically observed in MiLM.